Multifunctional current reference generation strategy for grid-tied power electronic converter - Bonaldo, Jakson Paulo; Paredes, Helmo Kelis Morales [UNESP]; Pomilio, José Antenor (Wydawnictwo SIGMA-NOT, 2015)
In this work the functionalities of Power Electronic Converters (PEC) used as grid interface device for distributed generation sources are extended to deal with Power Quality (PQ) issues. It is proposed an alternative strategy to obtain current references based on the Conservative Power Theory (CPT). The proposed strategy contributes to the full exploitation of the PEC power capacity, allowing the PEC to act as a multifunctional device performing simultaneously selective compensation of PQ issues and power injection into the utility grid.

Elektroniczny konwerter mocy PEC używany jako interfejs rozproszonych źródeł energii został poszerzony o możliwości poprawy jakości energii. Prądowe źródło odniesienia bazuje na Teorii Zachowania Mocy CPT.
Wielofunkcyjne prądowe źródło odniesienia do sieciowego konwertera mocy
Keywords: Multifunctional power converter; Power quality; Renewable power sources; Selective compensation; Konwerter mocy; Rozproszone systemy zasilania; Jakośc energii